sbx/KB-bert-base-swedish-cased_PI-detection-general - Szawerna, Maria Irena (University of Gothenburg, 2024)
A model based on KB/bert-base-swedish-cased trained to detect personal information, especially in learner essays. This variant differentiates between 7 general categories.

En modell baserad på KB/bert-base-swedish-cased tränad med syfte att upptäcka personliga uppgifter, särskilt i studentuppsatser. Den här varianten skiljer mellan 7 generella kategorier.
sbx/KB-bert-base-swedish-cased_PI-detection-general
Keywords: Language Technology (Computational Linguistics); PI detection; BERT; model; Natural Language Processing; Språkbehandling och datorlingvistik